Acquired Versus Congenital Neonatal Purpura Fulminans: A Case Report and Literature Review. Issue 8 (November 2018) - Findley, Tina; Patel, Minal; Chapman, John; Brown, Deborah; Duncan, Andrea F.
Abstract : Neonatal purpura fulminans (PF) is a life-threatening disorder caused by congenital or acquired deficiencies of protein C (PC) or S. PF presents as a cutaneous manifestation of disseminated intravascular coagulation. We describe a case of PF in a newborn with left leg ischemia and undetectable PC levels soon after birth. Despite anticoagulation therapy and PC concentrate, left foot amputation was required. Genetic testing of PROC for congenital PC deficiency was normal. This case highlights the course of PF due to acquired PC deficiency in a newborn treated with PC concentrate which is rarely described in the literature.